Analisis Pembentukan Revisi Undang-Undang Tentara Nasional Indonesia Perspektif Siyasah Dusturiyah - Muhammad Panji Hidayat; Relit Nur Edi; Abidin Latua (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the legislative process of the TNI Law and assess its conformity with the principles of siyasah dusturiyah, particularly the principle of deliberation (musyawarah). The research employs a normative legal method with a library-based approach, utilizing secondary data consisting of primary legal materials and secondary legal sources. The findings indicate that, from a normative–formal perspective, the formation of the TNI Law has complied with the stages of legislation as stipulated in the 1945 Constitution of the Republic of Indonesia and Law Number 12 of 2011 on the Formation of Laws and Regulations. However, from a procedural and democratic standpoint, the legislative process raises several serious concerns, particularly regarding the fulfillment of the principles of transparency and meaningful public participation. The relatively expedited legislative process, the limited dissemination of the academic draft and the bill, and the constrained space for dialogue with civil society and academic communities demonstrate that public participation was not optimally implemented as mandated by the Law on the Formation of Laws and Regulations and the Constitutional Court’s decisions on meaningful participation. Such limited participation is inconsistent with the principle of deliberation embodied in siyasah dusturiyah